Characterization and evaluation of the pozzolanic activity of granulated copper slag modified with CaO. (20th September 2019) - Feng, Yan; Yang, Qixing; Chen, Qiusong; Kero, Jakob; Andersson, Anton; Ahmed, Hesham; Engström, Fredrik; Samuelsson, Caisa
Abstract: GCS, granulated copper slag, is currently utilized in cement and concrete with a low rate, due mainly to its low pozzolanic activity. The present study was thus performed by first mixing the GCS with CaO, and then melting and water-granulating the GCS-CaO mixtures, as to enhance the reactivity of GCS. Blended cements were formulated by replacing 30 wt % of the cement, PC, with the modified GCS. The addition of CaO in GCS increased the release rates of heat from the early-age hydration of the blended cement pastes. The pastes with CSC20, the GCS of the highest CaO content (19.5%), acquired higher compressive strengths than those for the PC and other PC-GCS pastes at both 28 and 90 days of curing. The GCS richer in CaO consumed more calcium hydroxide for the formation of calcium silicate hydrates, with SEM micrographs showing a microstructure of more gel phases and less pores in PC-GCS paste. These results indicate that the modification by addition of CaO is an effective way to achieve a high reactivity for the GCS. It may then be possible to utilize the modified GCS as a high-quality supplementary cementitious material to enhance the sustainability for both copper and cement industries.